Employing artificial intelligence applications and their importance in the educational process from the point of view of computer teachers - Qirqaji, Ashwaq Dahman (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the reality of employing artificial intelligence applications and the degree of their importance in the educational process from the point of view of computer teachers, to achieve the objective of the research, the research was applied to a sample consisting of (54) male and female computer teachers affiliated with the Optimal Investment Program for Educational Cadres, A questionnaire was designed as a tool for collecting information consisting of (50) items, distributed over three axes, the validity and reliability of the questionnaire was confirmed, The Pearson correlation coefficient was used to calculate the internal consistency of the questionnaire and Cronbach alpha to calculate the stability coefficient, while the arithmetic means and standard deviations were used for the respondents’ responses to the research. The results of the research concluded that the level of computer teachers’ knowledge in employing artificial intelligence applications in the educational process came with a (high) degree With a arithmetical average (3.44 out of 5), the results also revealed that the reality of employing artificial intelligence applications in the educational process from the point of view of computer teachers came with a degree of (not agree) With an arithmetic average (2.36 out of 5), it was also concluded that there is a remarkable agreement on the importance of employing artificial intelligence applications in the educational process, and this result came with a degree of (important) With a arithmetical average (4.16 out of 5).